2014
DOI: 10.1016/j.afjem.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and skills of triage amongst nurses working in the emergency centres in Dar es Salaam, Tanzania

Abstract: significantly associated with age, weaning status and GCS of the patient (p < 0.05). Patients with lower GCS had higher chances of reintubation. Reintubation was not associated with sex, operation status and time of extubation. Conclusion: The rate of unwanted extubations and subsequent reintubations in Neuro ICU, can be decreased with protocol based monitoring, and through well maintained registers by neuro nurses. The knowledge of determinants of self extubation and the predictive factors of reintubation can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 18 publications
13
47
2
2
Order By: Relevance
“…Similar knowledge scores about triage were observed with nurses in EDs of other countries. A study done by Aloyce, Leshabari and Brysiewicz on assessment of knowledge and skills of triage amongst nurses working in the emergency centres in Dar es Salaam, Tanzania showed 33%of the respondents were not knowledgeable about triage but 67% were knowledgeable about triage which is in accordance with the current study [1]. The current study also agrees with the findings ofMalekshahi and Mohammad-zadeh in 2004, where nurses" knowledge level about triage was also a little above average (53.9%) [20]; and the study of Goransson, Ehrenberg and Ehnfors, which showed participants" knowledge level was 57.7% [19].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar knowledge scores about triage were observed with nurses in EDs of other countries. A study done by Aloyce, Leshabari and Brysiewicz on assessment of knowledge and skills of triage amongst nurses working in the emergency centres in Dar es Salaam, Tanzania showed 33%of the respondents were not knowledgeable about triage but 67% were knowledgeable about triage which is in accordance with the current study [1]. The current study also agrees with the findings ofMalekshahi and Mohammad-zadeh in 2004, where nurses" knowledge level about triage was also a little above average (53.9%) [20]; and the study of Goransson, Ehrenberg and Ehnfors, which showed participants" knowledge level was 57.7% [19].…”
Section: Discussionsupporting
confidence: 73%
“…Triage is an essential function of an Emergency Department (ED) and it is a term used to describe the sorting of patients for treatment priority in EDs [1]. The purpose and functionof triage is to first identify patients with life-threatening or emergency conditions who cannot wait to be seen and initiate appropriate interventions, and then allocate the patient to the right area within the ED [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Sungur et al (19) found that 64.7% of the nurses did not receive any triage training. A study by Aloyce et al (20) reported that 22% of the nurses working in EDs received nursing training in emergency care, whereas 78% had received no such training. However, the person who will do triage should know the symptoms of the diseases that require emergency intervention (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant limitation in research studies in the disaster medicine area is related to the lack of standards for collecting and reporting data [1]. The research tools are not validated [142], or available to use or utilizable during a disaster [138].…”
Section: Scientific Approachmentioning
confidence: 99%
“…Many hospitals in low-income countries lack a structured trauma system, including a formal triage system [138]. As an example, a study from Pakistan showed that 86% of pre-hospital personnel did not have a system for prioritizing patients and information to the hospital prior to arrival [139].…”
Section: Trauma Care and Triage In Low-and Middle-income Countriesmentioning
confidence: 99%